The The Effect of Green Entrepreneur Orientation on Network Resource Acquisition and Small and Medium Enterprises’ Business Performance with Knowledge Transfer and Integration and Green Technology Dynamism as Moderator Variables - Gazali Gazali; Zainurrafiqi Zainurrafiqi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
The purpose of this study is to examine the effect of green entrepreneur orientation on SMEs’ business performance with network resource acquisition as a mediating variable. The purpose of this study also examines the moderating effect of knowledge transfer and integration and green technology dynamism on the relationship between green entrepreneur orientation and SMEs’ business performance. This research is explanatory research that aims to test and explain the causal relationship between research variables through hypothesis testing. The approach used in this research is a quantitative research approach. The data is used in the form of primary data. The purposive sampling method was used as a sampling technique. The process of obtaining data was carried out by means of a survey in the form of a questionnaire. In this study, researchers used 180 Managers of SMEs who applied green entrepreneurs in four districts in Madura. This study uses Structural Equation Modeling (SEM) to test the hypothesis. The research finds that the influence of green entrepreneurial orientation has a positive influence on SMEs’ business performance and network resource acquisition. In addition, network resource acquisition is able to mediate the relationship between green entrepreneur orientation and SMEs’ business performance. Finally, knowledge transfer and integration and green technology dynamism are able to moderate the influence between green entrepreneur orientation and SMEs’ business performance.